2017
DOI: 10.5817/fai2017-2-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Brexit on European Equity Markets

Abstract: The aim of this paper is to give a comprehensive description of the risk dependence and interdependence between selected European stock markets and Brexit equity in the period spanning from January, 7, 2000 to February, 3, 2017 We have studied behavior of extreme quantiles using quantile regression approach. This approach is robust because it is based on the use of various measures of central tendency and dispersion statistics for a detailed analysis of the relationship between variables. We have found evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…We also used a dummy variable for post-Brexit periods; interestingly enough the related coefficient for Brexit is statistically significant for all stock markets, meaning that Brexit has led to at least 15% increase in volatility of FTSE, and 12% and 14% increase in DAX and CAC, respectively. The results here are consistent with those of Belke, Dubova, & Osowski [3] and Bohdalova, & Gregus [17], and Jackson, Akhtar, & Mix [14] who found that Brexit has led to higher volatility of stock market indices in EU.…”
Section: Estimated Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We also used a dummy variable for post-Brexit periods; interestingly enough the related coefficient for Brexit is statistically significant for all stock markets, meaning that Brexit has led to at least 15% increase in volatility of FTSE, and 12% and 14% increase in DAX and CAC, respectively. The results here are consistent with those of Belke, Dubova, & Osowski [3] and Bohdalova, & Gregus [17], and Jackson, Akhtar, & Mix [14] who found that Brexit has led to higher volatility of stock market indices in EU.…”
Section: Estimated Resultssupporting
confidence: 92%
“…Given, the detrimental role of Brexit for the volatility of stock markets, as emphasized by several economists including Bohdalova, & Gregus [17], and Belke, Dubova, and Osowski [3] this study tried to answer two main questions: (i) what are the effects of Brexit on three main stock market indices in Europe, FTSE, DAX, and CAC, using econometric models and a dummy variable for Brexit; and (ii) how can European Central Bank (ECB) react to stock market volatility and neutralize the adverse effects of Brexit on stock market indices. To respond to this question we used Taylor and Volker [21] model with embedded variables accounting for policy deviation in the traditional Taylor model, using depreciation of British pound and volatility of foreign stock market index.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical results show that under the influence of Brexit, flight-to-quality not only commonly occurs between the stocks and bonds of each country but also simultaneously occurs among different countries. Bohdalova and Greguš [5] give a comprehensive description of the risk dependence and interdependence between selected European stock markets and Brexit equity in the period spanning from January, 7, 2000 to February, 3, 2017. They apply quantile regression to study behavior of extreme quantiles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicate that the risk increased before the event due to political uncertainty; the return series differed with their reactions due to different characteristics of sectors to which the returns belonged to. A quantile regression approach with inclusion of the binary variable for the Brexit was used in Bohdalova and Greguš (2017). This research observed bigger European markets (German, French, Irish, Spanish) and bigger emerging ones (Polish and Turkish), with the time span ranging from beginning of 2000 until February 2017.…”
Section: Previous Related Researchmentioning
confidence: 99%